ChemInform Abstract: Nickel‐Catalyzed Cross‐Coupling of Functionalized Difluoromethyl Bromides and Chlorides with Aryl Boronic Acids: A General Method for Difluoroalkylated Arenes. Issue 9 (March 2015) - Xiao, Yu‐Lan; Guo, Wen‐Hao; He, Guo‐Zhen; Pan, Qiang; Zhang, Xingang
Abstract The first successful examples of Ni‐catalyzed difluoroalkylation of aryl boronic acids with difluoroalkyl bromides and chlorides is developed.